Ice age: investigating the impact of freezing and aging order on the palatability, physiochemical properties, and protein degradation of historically tough muscles - Dieball, Taylor (My University, 2025)
Beef is commonly aged and frozen to improve and preserve quality. While industry practices favor aging before freezing, some studies suggest freezing then aging may also be viable. This study evaluated how freezing and aging sequences affected consumer eating experience, physicochemical traits, and proteolysis in three muscles. Beef carcasses (N = 12; USDA Choice, A maturity) were collected from a Midwestern plant. Strip loins (Longissimus lumborum, LL), Semitendinosus (ST), and Biceps femoris (BF) were fabricated into 2.54-cm steaks and assigned to age-then-freeze (AF) or freeze-then-age (FA) for 21 or 28 days. Steaks were then assigned to one of the following designations: consumer sensory panels, Warner–Bratzler shear force, and lab assays. All steaks were aged before or after freezing between 1-4˚ C in the absence of light. Steaks were blast frozen before or after aging for 91 days at -20˚C. For all assays, samples were cooked to a peak internal temperature of 71˚C. The consumers (N = 192) evaluated samples for flavor, juiciness, tenderness, and overall liking, as well as acceptability for each sensory trait. On the following day, one steak from each muscle and treatment combination was evaluated for Warner–Bratzler shear force, cook loss, purge loss, and instrumental color. Freezing sequence and aging period did not affect (P > 0.05) consumer ratings of tenderness, flavor liking, or overall liking. However, unsurprisingly muscle type significantly influenced tenderness, flavor liking and overall liking, with the LL rated higher (P < 0.05) than the ST and BF. A freezing order × muscle × aging interaction was detected for juiciness (P < 0.05) in which the 28 d FA LL steaked resulted in the highest juiciness rating compared to all other muscles regardless of aging period or freezing treatment. Warner–Bratzler shear force confirmed LL as the most tender (2.76 kg; P < 0.05), with no difference (P > 0.05) between ST (4.06 kg) and BF (5.26 kg). There was an increase (P < 0.05) in purge loss in the FA compared to the AF samples (12.49% vs 8.57%). However, the FA samples had a lower (P < 0.05) percentage of cook loss compared to the AF samples (15.14% vs 16.31%). Desmin degradation revealed an interaction (P < 0.05) between freezing treatment and aging period across all muscles combined. Specifically, the 28-day, FA samples had a lower percentage (P < 0.05) of intact desmin compared to the 21 and 28-day, AF samples indicating more proteolytic activity occurred. This study found that reversing the freezing order did not impact the overall palatability of beef steaks from the loin or round. On the contrary, it led to a higher purge loss, increasing the potential for economic loss. Therefore, reversing the sequence of freezing and aging is not a viable strategy for the industry.
Keywords: Beef; Freezing; Palatability